2021
DOI: 10.3390/nano11051074
|View full text |Cite
|
Sign up to set email alerts
|

Holey Graphene: Topological Control of Electronic Properties and Electric Conductivity

Abstract: This paper studies holey graphene with various neck widths (the smallest distance between two neighbor holes). For the considered structures, the energy gap, the Fermi level, the density of electronic states, and the distribution of the local density of electronic states (LDOS) were found. The electroconductive properties of holey graphene with round holes were calculated depending on the neck width. It was found that, depending on the neck width, holey graphene demonstrated a semiconductor type of conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Thus, the presence of GNM with the triangle hole is highly improbable, it will be completed to holes of other geometric forms or will be filled by atoms of other types. By the original methodic, the virtual growing of CNT (11,10) from the obtained GNM supercells was performed. It was found that the growing of VACNT(11,10)-graphene from GNM with the circle form is the most energetically favorable since it has the lowest energy barrier 0.014 eV/atom.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the presence of GNM with the triangle hole is highly improbable, it will be completed to holes of other geometric forms or will be filled by atoms of other types. By the original methodic, the virtual growing of CNT (11,10) from the obtained GNM supercells was performed. It was found that the growing of VACNT(11,10)-graphene from GNM with the circle form is the most energetically favorable since it has the lowest energy barrier 0.014 eV/atom.…”
Section: Discussionmentioning
confidence: 99%
“…We chose CNT (11,10) for growing since it had the smallest radius from the most often synthesized CNTs [29][30][31]. Merging CNT and GNM was performed by the original methodic that provides building seamless junctions of carbon nanostructures [32].…”
Section: Virtual Growing Of Vacnt(1110)-graphenementioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] These 2D materials have received widespread attention because they exhibit outstanding features and properties in atomically thin 2D as compared with their bulk counterparts. [21][22][23][24][25][26][27][28][29] Their properties can be modified by chemical doping, creating vacancy/defect, or by the formation of heterostructures with the other 2D materials. [5,30,31] There is still a lot of scope for the search of other novel 2D materials with enchanting properties for their applications like electronics, DOI: 10.1002/adts.202200057 optoelectronics, spintronics, thermoelectric, gas sensing, storage, catalysis, etc.…”
Section: Introductionmentioning
confidence: 99%